Environmental Conditions in Estuaries of the Southeast United States: Long-Term Trends and Seasonal Drivers - Mallick, Nayan; Dunn, Robert P. (Ocean-land-atmosphere research, 2024)
Due to their location at the intersection of marine and freshwater ecosystems, estuaries are subject to the impacts of global change from both the ocean and land. Recent evidence has demonstrated numerous changes to environmental conditions within estuarine ecosystems, from increasing temperatures to changes in primary production, among others. We utilized long-term, high-temporal-resolution data on water temperature, salinity, dissolved oxygen, and chlorophyll-a concentrations in 3 National Estuarine Research Reserves in the southeast United States to characterize trends and seasonal drivers of estuarine water quality. We document spatiotemporal variability in long-term trends and seasonal patterns, with ubiquitous increases in water temperature over our study period (1995–2022) mainly driven by changes during winter months (December to February), concurrent with slight reductions in dissolved oxygen through time. We also document strong spatiotemporal variability in trends in salinity and chlorophyll-a concentration both across and within estuaries. Understanding the changes in biophysical conditions in estuarine ecosystems is critical to ensure our ability to predict the ecosystem functions and services estuaries can provide as climate conditions continue to change.